A CROSS-DISCIPLINARY APPROACH IN DEVELOPING SCHOOL RULES TO FOSTER STUDENTS' ISLAMIC CHARACTER AT AN INDONESIAN ISLAMIC SENIOR HIGH SCHOOL (MAN 4 KEDIRI) - Andi Sulistio (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
A cross-disciplinary approach in drafting regulations is an approach that combines various subjects from different groups to obtain new solutions that cannot be solved with one scientific discipline alone. This research is intended to analyze various scientific disciplines from different families in the preparation of rules and regulations using a cross-disciplinary approach and their impact on the formation of students' Islamic character. Data collection was carried out by observation, interviews and documentation studies. The data that has been recorded systematically is then condensed to make it easier to draw conclusions. The research results show that there are 8 different elements of scientific discipline, namely; PPKN, PAI, mathematics, language, biology, counseling guidance, sociology and law are contained in the madrasa regulations and summarized in the CAKEP book (Personality Notes). Compliance with the implementation of the agreed rules shows that students' Islamic character habits are increasing and can be seen in daily life in the madrasah environment.